2020
DOI: 10.1088/1742-6596/1517/1/012105
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of pH and oxygen sensors applied to aquaponic system

Abstract: Majority of agricultural activity in Indonesia still relies on rainwater for irrigation. In the dry season, there are many non-productive agricultural lands. It leads to decrease in farmers’ income. To solve this problem, Aquaponic Planting System was offered, but the system is complicated. It needs adequate oxygen and proper pH to make nitrification bacteria alive to convert NH3 to NO3- and NO2. Therefore, a system which controls oxygen and pH is needed. For pH calibration, a curve fitting method was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Once the research was carried out, we continue to find out the crucial parameters needed by shrimp within shrimp farms, where research conducted by Al Azzani AAH [2] showed the following: Once this information was collected, we proceeded to search for the sensors and actuators necessary to be able to carry out the work, for which it was decided to choose the following sensors that can be seen in Table II. Following the choice of sensors, it was decided which of the variables shown in Table I was the most important to automate, which chose to use dissolved oxygen in water., [7] since it has been proven to have direct effects on the growth and reproduction stages of shrimp, [1] for which a DC Z2D30-24A engine was chosen, which would allow us to perform the oxygenation process of the water when it reaches levels below what is desired.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Once the research was carried out, we continue to find out the crucial parameters needed by shrimp within shrimp farms, where research conducted by Al Azzani AAH [2] showed the following: Once this information was collected, we proceeded to search for the sensors and actuators necessary to be able to carry out the work, for which it was decided to choose the following sensors that can be seen in Table II. Following the choice of sensors, it was decided which of the variables shown in Table I was the most important to automate, which chose to use dissolved oxygen in water., [7] since it has been proven to have direct effects on the growth and reproduction stages of shrimp, [1] for which a DC Z2D30-24A engine was chosen, which would allow us to perform the oxygenation process of the water when it reaches levels below what is desired.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Then, the probability of each data is calculated using the normal distribution formula. To remove the outlier, we can use equation (5).…”
Section: 𝜷mentioning
confidence: 99%
“…The pH content in the water is the main parameter in determining whether or not the water is suitable for life. The influence of acidity levels on the development of organisms and microorganisms is dominant because, in fish and plant cultivation, the low pH level makes it difficult for beneficial microorganisms to grow [5]. The acidity level of water usually has a set point pH 3 -7, to support the fish growth ecosystem [3].…”
Section: Introductionmentioning
confidence: 99%
“…Kontrol PID yang digunakan pada mikrokontroller Arduino Nano digunakan untuk mengontrol frekuensi kecepatan motor aerator untuk mempertahankan nilai setpoint yang diinginkan untuk kadar oksigen pada kolam budidaya nila bioflok serta meminimalkan kesalahan pengukuran dan memastikan kestabilan kadar oksigen pada kolam budidaya. [10], [11]Data yang telah dihasilkan oleh sistem akan ditampilkan oleh LCD menggunakan protokol komunikasi I2C.…”
Section: Metode Penelitianunclassified